Modernisasi dalam Masyarakat Samin di Desa Klopoduwur Kecamatan Banjarejo Kabupaten Blora - Sujarwo, Joko; Muadzimah, Zumrotul; Wati, Diah Ayu Widya; Sutopo, Sutopo; Wirajaya, Asep Yudha (Pascasarjana IAIN Metro, 2023)
The desire to live in a more modern direction is evident in today's tribal traditions in Indonesia. The Samin community in Klopoduwur Village, Banjarejo District, Blora Regency is one of the tribes experiencing this condition. This study aims to determine modernization in the life of the Samin community in Klopoduwur Village, Banjarejo District, Blora Regency. This research includes a qualitative-descriptive study. The data in this study are in the form of utterances by predetermined informants, namely village officials, traditional leaders, and the general public; writings containing explanations about modernization and life of the Samin people. The research data were collected using interviews, observation, documentation, reading and note-taking techniques. The analysis model used in this paper is descriptive. The results of the study show that the social changes that occur in the Samin Klopoduwur community can be seen in the ideological, educational, economic, and political dimensions. Even though it seems that it is very binding for its adherents to continue to carry out Samin's teachings, currently, there is a relaxation of this obligation by the traditional elders of Samin Klopoduwur. This desire for modern life tends to be seen in the young Samin community in Klopoduwur.